Nilai-Nilai Estetika Zen pada Sushi di Wilayah Kansai - Rahmawati, Aulia; Lusiana, Yusida; Widodo, Heri (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2023)
This research aims to analyze the Zen aesthetic values contained in one of the traditional Japanese foods, sushi , especially  sushi  in the Kansai region. This research used descriptive qualitative method based on literature approach and documentation to collect relevant data. Theory used for this analysis is Zen aesthetic theory by Hisamatsu Shin'ichi. The conclusion of the analysis shows that sushi in the Kansai region, contains Zen aesthetic values in the characteristics of fukinsei (asymmetry), kokou (the essence of time), seijaku (tranquility) , yuugen (depth of meaning), shizen (naturalness), and Kansou (simplicity). These zen aesthetic values are contained in aspects of ingredients, cooking methods, serving methods, taste, and etiquette. The Japanese concepts found in this research are the concepts of moritsuke, ma, sasa giri, sugatamori, sugimori, chirashimori, hiramori, and goshiki .